Change in soil organic carbon between 1981 and 2011 in croplands of Heilongjiang Province, northeast China. (12th May 2015) - Li, Lu‐Jun; Burger, Martin; Du, Shu‐Li; Zou, Wen‐Xiu; You, Meng‐Yang; Hao, Xiang‐Xiang; Lu, Xin‐Chun; Zheng, Lin; Han, Xiao‐Zeng
Abstract: BACKGROUND: Soil organic carbon (SOC) is fundamental for mitigating climate change as well as improving soil fertility. Databases of SOC obtained from soil surveys in 1981 and 2011 were used to assess SOC change (0–20 cm) in croplands of Heilongjiang Province in northeast China. Three counties (Lindian, Hailun and Baoqing) were selected as typical croplands representing major soil types and land use types in the region. RESULTS: The changes in SOC density (SOCD) between 1981 and 2001 were −6.6, −14.7 and 5.7 Mg C ha −1 in Lindian, Hailun and Baoqing Counties respectively. The total SOC storage (SOCS) changes were estimated to be −11.3, −19.1 and 16.5% of those in 1981 in the respective counties. The results showed 22–550% increases in SOCS in rice ( Oryza sativa L.) paddies in the three counties, but 28–33% decreases in dry cropland in Lindian and Hailun Counties. In addition, an increase of 11.4 Mg C ha −1 in SOCD was observed in state‐owned farms ( P < 0.05), whereas no significant change was observed in family‐owned farms. CONCLUSION: Soil C:N ratio and initial SOCD related to soil groups were important determinants of SOCD changes. Land use and residue returning greatly affected SOC changes in the study region. To increase the topsoil SOCD, the results suggest the conversion of dry croplands to rice paddies and returning of crop residue to soils. © 2015 Society of Chemical Industry